PENGARUH IKLIM SEKOLAH TERHADAP KEDISIPLINAN BELAJAR PESERTA DIDIK KELAS X SMA NEGERI 7 PONTIANAK 2019/2020 - Resha Aulia; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2021)
AbstractAtmosphere of school climate or state of a school, related to the discipline of learning which can be influenced by the school climate. This research aims to describe the influence of school climate on the discipline of learning of class X SMA Negeri 7 Pontianak. This research method used a descriptive method with the form of influence study research. Data collection techniques in this study are indirect communication techniques and data collection tools using a questionnaire. Based on the results of data analysis, it shows for us that the climate of SMA Negeri 7 Pontianak is in a very good category, with a percentage of 85.01%. Value of the discipline of learning class X SMA Negeri 7 Pontianak in a good category with a percentage of 77.16%. There is a significant influence that is equal to 47% of the school climate of disciplinary learning in class X SMA Negeri 7 Pontianak. The higher the school climate, the higher the level of discipline of students in class X SMA Negeri 7 Pontianak in learning and vice versa, the lower the school climate, the lower the level of learning discipline of students in class X SMA Negeri 7 Pontianak in learning.Keyword : Clime, Discipline, Learning